The role of metformin in treatment of weight gain associated with atypical antipsychotic treatment in children and adolescents: A systematic review and meta-analysis of randomized controlled trials - Mansuri, Zeeshan; Makani, Ramkrishna; Trivedi, Chintan; Adnan, Mahwish; Vadukapuram, Ramu; Rafael, John; Lodhi, Ashutosh; Reddy, Abhishek (Frontiers in Psychiatry, 2022)
Introduction Second-generation antipsychotics are associated with significant weight gain. The aim of this systematic review and meta-analysis was to determine the efficacy and safety of metformin for the treatment of weight gain in children and young adults treated with second-generation antipsychotics. Methods We followed PRISMA guidelines to evaluated studies published before March 2020 in Medline, Google Scholar, PubMed, Cochrane library database, annual scientific sessions of the American Psychiatric Association, American Academy of Child and Adolescent, Psychiatry, and American Society of Clinical Psychopharmacology. Studies included compared metformin with the placebo for management of weight gain in children and adolescents taking atypical antipsychotics. Non-randomized studies, animal experiment studies, editorials, and review studies were excluded. Multiple parameters, including change in anthropometric-biochemical parameters, drug discontinuation rate, and side effects among the groups were assessed. The random-effects method was used for meta-analysis. Results Four studies with were included in the final analysis (213 patients; metformin: 106; control: 107). After pooled analysis, 12–16 weeks of metformin therapy was associated with a significant reduction in weight [(mean difference (MD): −4.53 lbs, confidence interval (CI): −6.19 to −2.87, p-value < 0.001)], and BMI z score [MD, −0.09, CI: −0.16, −0.03, p-value: 0.004] compared to control. Metformin was also associated with a significant reduction in insulin resistance [MD: −1.38, CI: −2.26 to −0.51, p-value: 0.002]. There were higher odds of nausea-vomiting [OR: 4.07, CI: 1.32–12.54, p-value: 0.02] and diarrhea [OR: 2.93, CI: 1.50–5.71, p-value: 0.002] in the metformin group. However, there was no difference in drug discontinuation rate [OR: 1.45, CI: 0.41–5.06, p-value: 0.56]. Conclusion Metformin may prove beneficial in the treatment of weight gain in children treated with second-generation antipsychotics. The pooled treatment effect showed a significant reduction in BMI Z-score and weight in just 12–16 weeks. The limitations include small sample size, variation in metformin dose, and duration of treatment. This meta-analysis should be interpreted as promising, and further larger studies are warranted before drawing a conclusion.